Pemulihan Ekonomi Keluarga Pasca Bencana Tsunami Selat Sunda Di Desa Bulakan Kecamatan Cinangka Kabupaten Serang Melalui Penciptaan Nilai Tambah Pisang Coklat Crunchy - Purnamasari, Ratih; Salam, Anis Fuad; Suseno, Bambang Dwi (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
The processing and utilization program of banana in the village of Bulakan is motivated by the efforts to restore the family's economy after the Sunda Strait tsunami disaster. One of the great potentials that has not been well utilized for economic purposes in the village of Bulakan is banana. The solution offered is the processing and utilization of bananas to be processed products. The purpose of this program is to provide both knowledge and skills to the people of Bulakan Village in processing bananas into crunchy chocolate bananas so that the management of processed banana products becomes a good and sustainable management system as well as improving the economy. The method used to overcome these problems through the problem identification, socialization, training in the cultivation of bananas, marketing, reflection and evaluation. The program was carried out in July 2019 in Bulakan Village, Cinangka District, Serang Regency, Banten. An important change in society is changing the community paradigm from selling bananas directly to processing bananas into crunchy chocolate banana products.